TINGKAT KETEPATAN ADOPSI PETANI TERHADAP SISTEM TANAM JAJAR LEGOWO PADA TANAMAN PADI SAWAH (Studi kasus di Desa Undaan Kidul, Kecamatan Undaan, Kabupaten Kudus) - Wahyu Aji Hidayatulloh; Suprapti Supardi; Lutfi Aris Sasongko (MEDIAGRO, 2012)
Paddy is the raw material of rice, where rice is a basic need that is important. Faltering rice self-sufficiency should be sought immediately find a way out, including technology that can answer these problems. One form of technology in the agricultural sector is to improve farming methods and the use of improved seed. The way that to do by farmers to renew farming especially in Kudus is by adopting innovation Jajar Legowo cropping system which is an integrated development concept pioneered by Centers of Agricultural Technology Research (BPTP) in Central Java. The purpose of this study were to determine the accuracy level of the farmer’s adoption in Jajar Legowo cropping systems at Undaan District and to know the problems that occur in Jajar Legowo cropping systems at Undaan District. The village was used as research is Undaan Kidul village, as the village has adopted the Jajar Legowo cropping systems. Taking a sample of farmers conducted in purposive sampling (a total of 100 people who will serve as the respondents in this study). Accuracy level of innovation adoption Jajar Legowo cropping systems in all aspects of belonging to the right (89,75%). This means that most of the respondent farmers have applied as recommended from every aspect of the Jajar Legowo cropping systems in paddy plant. The problems that arise in the innovation adoption of Jajar Legowo cropping system is the aspect of inspection because the aspects of the examination requires special expertise and thoroughness of farmers to examine in detail the condition of their grain crops. Keywords: Jajar Legowo, Adoption, Paddy